2015
DOI: 10.1051/0004-6361/201425032
|View full text |Cite
|
Sign up to set email alerts
|

(Sub)millimetre interferometric imaging of a sample of COSMOS/AzTEC submillimetre galaxies

Abstract: We used the Plateau de Bure Interferometer (PdBI) to map a sample of 15 submillimetre galaxies (SMGs) in the COSMOS field at the wavelength of 1.3 mm. The target SMGs were originally discovered in the James Clerk Maxwell Telescope (JCMT)/AzTEC 1.1 mm continuum survey at S/N 1.1 mm = 4−4.5. This paper presents, for the first time, interferometric millimetre-wavelength observations of these sources. The angular resolution of our observations, ∼1. 8, allowed us to accurately determine the positions of the target … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 48 publications
(85 citation statements)
references
References 153 publications
(208 reference statements)
3
82
0
Order By: Relevance
“…We explore two intrinsic number counts that are intended to bracket the plausible range of values for DSFGs based on two interferometric surveys. One is the number counts measured in ALESS , and the other is from interferometric follow-up of the first AzTEC survey in COSMOS (Scott et al 2008) using the SMA (Younger et al 2007(Younger et al , 2009) and PdBI (Miettinen et al 2015). These interferometric observations have shown that all of the sources in their surveys are either unlensed or lensed by magnification factors 2 < (a similar result is found based on ALMA imaging of 52 DSFGs in the Ultra Deep Survey; Simpson et al 2015).…”
Section: Statistical Predictions For μ 870mentioning
confidence: 52%
See 2 more Smart Citations
“…We explore two intrinsic number counts that are intended to bracket the plausible range of values for DSFGs based on two interferometric surveys. One is the number counts measured in ALESS , and the other is from interferometric follow-up of the first AzTEC survey in COSMOS (Scott et al 2008) using the SMA (Younger et al 2007(Younger et al , 2009) and PdBI (Miettinen et al 2015). These interferometric observations have shown that all of the sources in their surveys are either unlensed or lensed by magnification factors 2 < (a similar result is found based on ALMA imaging of 52 DSFGs in the Ultra Deep Survey; Simpson et al 2015).…”
Section: Statistical Predictions For μ 870mentioning
confidence: 52%
“…4. Intrinsic number counts for DSFGs with a form that matches observations in COSMOS (Miettinen et al 2015) underpredict the number of lensed sources with apparent S 10 mJy 870 > . Number counts based on ALESS observations provide a better match to our magnification measurements.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…The spectroscopic program targeted two additional galaxies, C1-2127 and C1-19764, consistent with being at z 3  but not originally included in the sample presented in Marchesini et al (2010) because they did not strictly satisfy the completeness limit in stellar mass (though both massive with log (M M 11.2 11.3 * ) -). Table 1 also lists C1-21316 from the sample of Marchesini et al (2010) but not targeted by our spectroscopic follow-up program, since it has a previously confirmed spectroscopic redshift of z 3.971 spec = Smolčić et al 2012; but see also Miettinen et al 2015). Table 1 Ground-based Spectroscopic Observations Notes.…”
Section: Target Selectionmentioning
confidence: 99%
“…), 6 GHz VLA (Myers et al, in prep. ), and the deep multiwavelength X-ray to mm photometry (Scoville et al 2007;Koekemoer et al 2007;Hasinger et al 2007;Capak et al 2007;Sanders et al 2007;Bertoldi et al 2007;Elvis et al 2009;Ilbert et al 2013;McCracken et al 2012;Scott et al 2008;Aretxaga et al 2011;Smolčić et al 2012;Miettinen et al 2015;Civano et al 2016;Laigle et al 2016, Capak et al, in prep. ) and more than 97 000 optical spectroscopic redshifts (Salvato et al, in prep.…”
Section: Introductionmentioning
confidence: 99%